Establishment of a pop-up library as an extension service of a public library - Talag, Rima Paulyn E. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Public libraries are an essential part of every city, it is known to contribute greatly to the knowledge and skills of a community. In the Philippines, as of 2008, there are a total of 1157 public libraries around the country. This is supported by the Republic Act 7743 implemented in 1994, that dictates that public libraries in the Philippines are a must and that its main role is to improve literacy in the country.